TUTUNGKUSAN SISTEM PENGETAHUAN EKOLOGI, DALAM MUSIK SUNDA: Revitalisasi Pengetahuan Ekologi pada Tarawangsa Berbasis UU Pemajuan Kebudayaan - Fauzi, Yudi Nurman (Paraguna, 2021)
Cultural inheritance in Sundanese society and the archipelago in general is often done through non-written media. Some of the noble values of the old society were passed down to the next generation through symbols, including through literary language, songs, and even through offerings. No exception in the inheritance of knowledge systems about ecology, including the lifestyle of Sundanese people with their environment which tends to have an agrarian lifestyle, old values are inherited by performing arts media, one of which is through tarawangsa, in which there is a ritual procession that displays a variety of symbols that have different meanings. Mark. In some cases, the existence of surviving art is not in line with the values that exist in it, so that revitalization efforts are needed, not in the form or material of the performance, but on the values inherited by the predecessors. In the local language, the inheritance of these values is known as "tutungkusan". In line with the enactment of the Cultural Advancement Law or Law 5 2017, various local values, including oral knowledge to art, are legally protected, and even encouraged to continue to be developed. On the other hand, today's situation is related to ecology, modern society has a high enough challenge in dealing with environmental degradation. In the position of exploring or revitalizing local knowledge in traditional Sundanese music (tarawangsa), this paper aims to extract knowledge values related to ecology that exist in the art of tarawangsa which in the view of the Law on the Advancement of Culture, is important to be actualized again.